Environmental sustainability reporting and practices of Publicly Traded Companies in Czech Republic - Suchoňová, Katarína; Tyll, Ladislav; Ryška, Tomáš, 1976-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2020)
This paper describes the overall results from an evaluation of how publicly traded companies in the Czech Republic report their environmental sustainability whilst also assessing what areas of environmental sustainability they focus on. A descriptive research design was chosen for this paper. Throughout the paper, a crucial research problem was the level of scarcity in publicly traded companies in the Czech Republic. Therefore, the sample used consisted of sixteen publicly traded companies. However, only twelve of those companies were analysed due to the availability of their non-financial reports that address environmental sustainability. One significant finding concluded from the paper established that most companies published a non-financial report relating to sustainability separately rather than including it in their annual report. In addition, the research found that half of the companies reported their non-financial information following the Global Recording Initiative. Furthermore, five main areas of environmental sustainability were identified with the use of coding among the companies: energy, emissions, water, waste, biodiversity. Overall, for most of the companies, their main focus area was energy; this result was supported by a frequency of words analysis. The analysis showed that the most frequently used word in all the reports was “Energy”. In conclusion, publicly traded companies in the Czech Republic all report non-financial information as required by the Directive 2014/95/EU. Most of the reports were easily readable, with clearly set out goals for environmental impact improvements. However, there were some companies that lacked to clearly identify the actions they would take in order to support their goals. This is an area where these companies could improve, allowing them to inform their stakeholders further about their environmental practices.
Vedoucí práce: Ladislav Tyll
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: business administration/corporate finance and management [obor bakal. práce]; bakalářské práce; bachelor's theses